Zinc - air microbial fuel cell from fungal degration of oil palm empty fruit bunch - Wan Nur Asiah Wan Mohd Shukri (Kulliyyah of Engineering, International Islamic University Malaysia, 2021)
The main stumbling block for practical implementation of bioenergy harvesting is the low energy gain yields (output/cost). Therefore, the challenge is to reduce the complexity of the cell design, minimize its control features and at the same time increase the energy output. The present work describes a bioelectrochemical system that adopts simple design configurations, operates in uncontrolled ambient surrounding and sustains a constant current output 1mA for 44 days. The microbial fuel cell (MFC) comprises of white rot fungus of Phanaerochaete chrysosporium fed with oil palm empty fruit bunch (EFB) agrowaste as the substrate. Unlike most MFCs, the fungal inoculums were not cultured on the current collector but left to be freely suspended in unbuffered potato dextrose broth (PDB) electrolyte. This fungal strain degrades lignin by producing ligninolytic enzymes such as laccase. Laccase demonstrates specific affinity for oxygen as its electron acceptor. By simply pairing zinc and air electrode in a membraneless, single chamber 250 ml enclosure, electricity could be harvested as the fungal microbes degrade the lignin-rich agrowaste. The microbial zinc/air cell was capable to sustain a 1 mA discharge current for 44 days continuously i.e. a 1056 mAh discharge capacity. The role of metabolic activities of P. chrysosporium on EFB towards the MFC performance was supported by linear sweep voltammetry measurement and scanning electron microscopy observations on lignin transformation during degradation. Scaling-up the bioelectrochemical system pose yet another challenge because biological processes of living microbes cannot be simply enhanced by incorporating more nutrients or substrate. This work investigated several aspects to increase the power density of an MFC. The factors studied were cathode surface area, volumetric capacity, cell stacking (series and parallel) and also a novel cell configuration. By increasing the cathode surface area substantially and pairing the cells in parallel, a 20-litre MFC prototype could deliver a 24 Ah discharge capacity, rated at 20 mA. The MFC however, is not economically viable. Using a novel cell configuration, the dependency on the air cathode was reduced and yet the MFC possessed much better discharge performance. A 5-litre prototype rated at 5 mA, demonstrated a discharge capacity of 2.2 Ah with an average operating voltage of 0.8 V. In conclusion, novel cell configuration is the most suitable design for scale up as it require less air cathode, smaller size and less volumetric capacity.